1993
DOI: 10.1055/s-2007-1002054
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Oral Glucose Loading on the Renin-Angiotensin-Aldosterone System in Patients with Chronic Renal Disease

Abstract: To determine the changes of the glucose-induced renin-angiotensin-aldosterone system in chronic renal disease, a standard oral glucose loading test (75g) was performed in patients with chronic glomerulonephritis (CGN) (n = 12) and compared with control subjects (10). Glucose loading resulted in a significant decrease of serum aldosterone as well as increases of blood glucose and insulin similarly in both CGN and C. However, the suppression of aldosterone was statistically milder in CGN than in C (p < 0.05). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…High aldosterone levels were noted in G2 patients serving as controls with normal potassium levels. Chronic glomerulonephritis was the main cause of their primary renal disease and high aldosterone and renin levels, suggestive of secondary hyperaldosteronism due to autonomous renin secretion in this renal disease, as other investigators have found (13,14) could explain this phenomenon.…”
Section: Discussionmentioning
confidence: 67%
“…High aldosterone levels were noted in G2 patients serving as controls with normal potassium levels. Chronic glomerulonephritis was the main cause of their primary renal disease and high aldosterone and renin levels, suggestive of secondary hyperaldosteronism due to autonomous renin secretion in this renal disease, as other investigators have found (13,14) could explain this phenomenon.…”
Section: Discussionmentioning
confidence: 67%